An Unusual Case of Metastatic Follicular Thyroid Cancer 40 Years after Initial Diagnosis - Lakshmi Pakath Menon; Spyridoula Maraka (Case Reports in Endocrinology)
Thyroid cancer recurrence can occur decades after initial diagnosis despite excellent response to therapy. Thyroid cancer recurrence is evaluated using serum thyroglobulin (Tg) and imaging studies including I-131 WBS and neck ultrasound. Limitations in Tg measurement and WBS may result in failure to detect recurrence. We report the case of a 63-year-old man who was noted to have rhonchi during a routine visit. He had a past history of follicular thyroid cancer that was diagnosed 40 years ago and treated with total thyroidectomy and radioactive iodine. He had excellent response to therapy with undetectable Tg levels, normal neck ultrasounds, and multiple negative whole body scans (WBS) due to which he was discharged from endocrinology clinic after 37 years of follow-up. Chest X-ray revealed a left lung mass with biopsy positive for thyroid cancer. Tg remained undetectable with negative anti-Tg antibody. Left pneumonectomy was done which revealed a mix of 70% differentiated thyroid cancer and 30% poorly differentiated/anaplastic thyroid cancer. He received two cycles of Doxorubicin and Paclitaxel. At 4 months follow-up after surgery, he had 3 subcentimeter nodules in his right lung. This case highlights that physical exam remains an essential tool to evaluate for recurrence. Since the lungs are the most common site of metastasis in follicular thyroid cancer, a chest X-ray may help detect metastasis that is missed on other modalities.